The Impact of Laughter Therapy on Heads of Division and Sub Division of Unesa - Suyono, Suyono (Universitas Negeri Surabaya, 2021)
The purpose of this laughter therapy is to increase the level of happiness of the therapy targets, namely Heads of Division and Head of Sub Division of Unesa. The number of targets for laughter therapy was 51 people. Increasing the scale of happiness is assumed to have an impact on increasing the body's immunity, so this laughter therapy can be an effort to prevent the Covid-19 attack which is currently pandemic. Methods of implementing the activity: (1) preparation of a happiness scale questionnaire instrument, (2) preparation of funny videos, and (3) implementing laughter therapy. The design of the activity implementation adopted the research paradigm of the One-Group Pretest-Posttest Design. The data analysis of changes in the happiness scale used Wilcoxon's non-parametric statistical analysis techniques and was assisted by SPSS. The results achieved: (1) the Happiness Scale Questionnaire Instrument has been successfully created, which is packaged in the form of a google-form, (2) 15 funny videos that meet the criteria are not contra-educational and free from elements of violence, SARA, and pornography) which are collected on flash drives and on Google Drive, and (3) laughter therapy activities have a positive impact on the happiness scale of the Head of Sub-Section of Unesa, there was a significant increase.